Disruption of the fibroblast growth factor-2 gene results in decreased bone mass and bone formation - Aldemar Montero; Yosuke Okada; Masato Tomita; Masako Ito; Hiroshi Tsurukami; Toshitaka Nakamura; Thomas Doetschman; J. Douglas Coffin; Marja M. Hurley (The Journal of Clinical Investigation, 2000)
Basic fibroblast growth factor (FGF-2), an important modulator of cartilage and bone growth and differentiation, is expressed and regulated in osteoblastic cells. To investigate the role of FGF-2 in bone, we examined mice with a disruption of the Fgf2 gene. Measurement of trabecular bone architecture of the femoral metaphysis of Fgf2+/+ and Fgf2–/– adult mice by micro-CT revealed that the platelike trabecular structures were markedly reduced and many of the connecting rods of trabecular bone were lost in the Fgf2–/– mice. Dynamic histomorphometry confirmed a significant decrease in trabecular bone volume, mineral apposition, and bone formation rates. In addition, there was a profound decreased mineralization of bone marrow stromal cultures from Fgf2–/– mice. This study provides strong evidence that FGF-2 helps determine bone mass as well as bone formation.